Characteristics of Primary Bradyarrhythmia in Hypertrophic Cardiomyopathy: A 10-Year, Single-Center Analysis - Hong-Da Zhang; Min Tang; Jing-Tao Zhang (Journal of Cardiovascular Development and Disease, 2022)
Background: Secondary bradyarrhythmias in hypertrophic cardiomyopathy (HCM) have been extensively reported. The prevalence and characteristics of primary bradyarrhythmias in HCM have yet to be investigated. Methods: We retrospectively enrolled 101 consecutive patients with HCM who were referred to the arrhythmia center from May 2010 to October 2020. The clinical features of patients with bradyarrhythmias were analyzed. Results: Twenty-nine (28.7%) patients had primary bradyarrhythmias, and six (5.9%) patients had secondary third-degree atrioventricular block (AVB). Of the 29 patients, 17 (58.6%) had sinus node dysfunction (SND), 14 (48.3%) had AVB, and two (6.9%) had both SND and AVB. The median age was 62 years old, and 69% were male. Six (20.7%) patients had left ventricular obstructive outflow tract obstruction, 15 (51.7%) had a history of syncope, and one (3.4%) had a family history of HCM. Most patients (86.2%) had New York Heart Association functional class I or II, and the median left ventricular ejection fraction was 63%. A total of 22 patients received pacemaker implantation, including 17 (77.3%) dual-chamber pacing, four (18.2%) single-chamber ventricular pacing, and one (4.5%) cardiac resynchronization therapy. Conclusions: Primary bradyarrhythmias need to be evaluated in HCM patients with arrhythmia-related symptoms. Patients with HCM might need pacemaker implantation for primary bradyarrhythmias.